Aggressive recurrent intestinal-type adenocarcinoma of the nasal cavity: a case report and literature review - Chen, YaoYao; Xu, Jiawei; Yu, Chengdong; Shi, Haoyu; Luo, Ling; Peng, Dingbang; Zhang, Xiaofang; Chen, Wen; Le, Fei (Frontiers in Medicine, 2025)
Intestinal-type adenocarcinoma (ITAC) of the nasal cavity is a rare, aggressive tumor that presents unique therapeutic challenges, particularly in cases of recurrent disease with intracranial extension. We present the case of a 54-year-old male with recurrent ITAC who demonstrated a remarkable response to a novel triple-therapy approach. This patient lacked the typical risk factors, such as occupational exposure to wood or leather dust, making this case particularly unusual. After failing conventional treatments and experiencing multiple recurrences with progressive intracranial invasion, the patient received an innovative combination of immunotherapy (Toripalimab), targeted therapy (Anlotinib), and chemotherapy (S-1). This unprecedented therapeutic combination resulted in significant tumor volume reduction (from 53.9 × 42.7 mm to 38.9 × 18.8 mm) and marked improvement in neurological symptoms, particularly diplopia. To our knowledge, this represents the first case report of successful implementation of this specific triple therapy regimen for recurrent ITAC with intracranial extension.